Profil Darah Kambing Lokal Betina yang diberi Silase Campuran Sorghum Daun Gamal dan Konsentrat dengan Perimbangan Level yang Berbeda - Odo, Remigius Abha; Matahine, Thomas; Kihe, Johny Nada (Yayasan Sumber Daya Manusia Cerdas, 2025)
A study was conducted to determine the blood profile of female local goats that were given a mixture of sorghum gamal leaf silage and concentrate with different balance levels. The study used female local goats aged 6 to 8 months. An experimental method was employed, utilizing a Latin square design with four treatments and four periods. The treatments were as follows: 80% silage + 20% concentrate (P0), 70% silage + 30% concentrate (P1), 60% silage + 40% concentrate (P2), and 50% silage + 50% concentrate (P3). Parameters measured included erythrocytes, leukocytes, hematocrit, and hemoglobin. The data obtained were tabulated and analyzed using analysis of variance (ANOVA). The overall average values of each variable in each treatment were as follows: erythrocyte concentration: P0 = 10.69 ± 0.01; P1 = 10.70 ± 0.13; P2 = 10.64 ± 0.08; P3 = 10.60 ± 0.13; leukocyte concentration: P0 = 10.93 ± 0.26; P1 = 10.98 ± 0.16; P2 = 10.99 ± 0.21; P3 = 10.96 ± 0.16; hematocrit concentration: P0 = 31.65 ± 0.86; P1 = 32.24 ± 0.94; P2 = 31.95 ± 1.11; P3 = 31.58 ± 0.85; hemoglobin concentration: P0 = 10.55 ± 0.16; P1 = 10.75 ± 0.25; P2 = 10.65 ± 0.39; P3 = 10.53 ± 0.41. The results indicated that the treatment had no significant effect (P > 0.05) on erythrocyte, leukocyte, hematocrit, or hemoglobin values. It was concluded that goats consuming a silage ration mixed with sorghum gamal leaf and concentrate at various balance levels of 20:80, 30:70, 40:60, and 50:50 displayed similar values for erythrocytes, leukocytes, hematocrit, and hemoglobin, with each value falling within the normal range.